2022
DOI: 10.1145/3488307
|View full text |Cite
|
Sign up to set email alerts
|

How Good is Good Enough? Quantifying the Impact of Benefits, Accuracy, and Privacy on Willingness to Adopt COVID-19 Decision Aids

Abstract: An increasing number of data-driven decision aids are being developed to provide humans with advice to improve decision-making around important issues such as personal health and criminal justice. For algorithmic systems to support human decision-making effectively, people must be willing to use them. We expand upon prior research by empirically modeling how accuracy and privacy influence intent to adopt algorithmic systems, focusing on an globally-relevant decision context with tangible consequences: the COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 64 publications
3
29
2
Order By: Relevance
“…These people seemed to prefer decentralized designs over centralized designs. This finding aligns with a study by Kaptchuk et al [7] that found 27% of people do not want to install COVID contact-tracing apps even if they are perfectly private (Section 4.3). • The most popular app design (centralized, release infection hotspots in public places) had around 55% of our participants willing to install (Section 4.1).…”
Section: Collect Location History Of Infected Userssupporting
confidence: 91%
See 2 more Smart Citations
“…These people seemed to prefer decentralized designs over centralized designs. This finding aligns with a study by Kaptchuk et al [7] that found 27% of people do not want to install COVID contact-tracing apps even if they are perfectly private (Section 4.3). • The most popular app design (centralized, release infection hotspots in public places) had around 55% of our participants willing to install (Section 4.1).…”
Section: Collect Location History Of Infected Userssupporting
confidence: 91%
“…They can also gather information to help epidemiologists monitor the spread of the disease, discover disease hotspots, and contact exposed individuals. However, their effectiveness is highly dependent on the adoption rate, which has been demonstrated to be challenging due to people's concerns about issues such as privacy [5,6,7]. Ferretti et al [8,9] suggested that if 60% of the population installed the app, the estimated number of coronavirus cases would go down.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a baseline scenario, without improvements to detection specificity, every user would spend over two days a month on average incorrectly quarantining, and ∼40,000 to ∼65,000 additional confirmatory lab-based tests would be required each day. The social and economic harm caused by solely promoting uptake or adherence without improvements to detection specificity would likely undermine public confidence in and compliance with a wearable-based pandemic mitigation strategy 22 . Alavi et al found that many false positives were due to the detection algorithm identifying lifestyle- driven changes in resting heart rate (e.g., after intense exercise or alcohol consumption); accounting for these factors using more advanced algorithms may be one way to target improved detection specificity 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Third, we made the simplifying assumption that all users without symptoms (and that no users with symptoms) could benefit from wearable-informed prompts to take a confirmatory test and self-isolate. Fourth, we did not consider how uptake or adherence might vary over time or with detection accuracy 18,22 . Fifth, we used median values for SARS-CoV-2 infection parameters (e.g., latent period) and did not account for reinfections or vaccinations.…”
Section: Discussionmentioning
confidence: 99%